تباين الإصابات الرياضية للاعبى التنس وعلاقتها بنوعية أرضيات الملعب - محمد، حسين فؤاد جاب الله; طلعت، أحمد هانى أحمد (جامعة حلوان - كلية التربية الرياضية للبنين, 2013)
تهدف الدراسة إلى التعرف علي تباين الإصابات الرياضية للاعبى التنس وعلاقتها بنوعية أرضيات الملعب من خلال التعرف على أكثر أنواعها ، مناطق وفترة حدوثها , وتحديد أكثر أنواع أرضيات الملعب التى تحدث بها الإصابات (الترابية – الصلبة). وقد تم استخدام الاستبيان كأداة لجمع البيانات والمنهج الوصفى لملائمتة وطبيعه هذه الدراسة, وأجريت الدراسة على عينة من لاعبى التنس من الناشئين المصنفين من(14: 16 سنة)، والمشاركين فى بطولات الاتحاد خلال الموسم الرياضى2013م، وتم اختيار العينة بالطريقة العمدية ، وبلغت (39) من لاعبى التنس الذين تعرضوا للإصابات الرياضية المختلفة خلال ممارسة نشاط التنس, وقد أسفرت النتائج على ما يلى :-- \ - أكثر أنواع الإصابات لدى اللاعبين فى الملاعب الترابية هى الشد العضلى ، يليها الالتواء ، ثم التمزق ، وأقلها الكسور \ - أكثر أنواع الإصابات لدى اللاعبين فى الملاعب الصلبة هى الالتواء ، يليها الشد العضلى ، ثم التمزق ، وأقلها الكسور \ - أكثر مناطق حدوث الإصابات لدى اللاعبين فى الملاعب الترابية هى الساق ، يليها الكاحل ، ثم الفخذ ، وأقلها ألم الكعب. \ - أكثر مناطق حدوث الإصابات لدى اللاعبين فى الملاعب الصلبة هى الكاحل، يليها الفقرات القطنية، ثم الساق والفخذ ، وأقلها ألم الكعب . \ - أكثر توقيتات فترة حدوث الإصابات لدى لاعبى التنس فى المنافسات عن التدريب. \ - أكثر أرضيات الملعب استخداماً لدى اللاعبين فى التدريب هى الترابية ، والملاعب الصلبة كانت هى الأكثر استخداماً فى المنافسات. \ - زيادة انتشار الإصابات لدى لاعبى التنس تبعاً لأرضية الملعب فكانت على الملاعب الصلبة بنسبة أكبر. The study aims to identify the variation of sports injuries for tennis players and their relationship with the quality pitch through the identification of more types, regions and the period occurring , and to identify the most common types of pitch that occur by injuries ( dirt - solid) . The questionnaire has been used as a tool for data collection and descriptive approach for relevance and the nature of this study. The study was conducted on a sample of tennis players from beginners classified from (14 : 16 yrs), and participating in tournaments Union during the sports season of 2013 , it was chosen randomly, amounted to (39) of tennis players who have been subjected to various sports injuries during the exercise activity tennis , the results were as : \ -\ The most common types of injuries to the players in the clay are cramps , followed by sprains , Rip, least of fractures. \ -\ The most common types of injuries to the players in the hardcourt are sprains, followed by cramps , then rupture , and least of fractures. \ -\ More areas of injury to the players in the clay is the leg, followed by the ankle , thigh , and least of heel pain . \ -\ More areas of injury to the players in the hardcourt is the ankle, followed by the lumbar spine , then the leg and thigh , and least of heel pain . \ -\ Over the timing of the incidence of injuries to tennis players in training for competitions . \ -\ The most commonly used pitch to the players in training is dirt , and the hardcourt is the most commonly used in competitions. \ -\ Increasing the prevalence of injuries among tennis players according to the pitch was on hardcourt greater proportion .
Keywords: الإصابات الرياضية -- لاعبو التنس -- ارضيات الملاعب -- التدريب الرياضي